2021
DOI: 10.1111/jre.12882
|View full text |Cite
|
Sign up to set email alerts
|

Variations in IgG antibody subclass responses to oral bacteria: Effects of periodontal disease and modifying factors

Abstract: Background and objective Local and systemic IgG antibodies or oral bacteria have been described with periodontitis. We extended these observations by assessing the impact of a range of intrinsic factors on serum IgG subclass antibodies to both commensal and pathogenic oral bacteria that would contribute to variations in immune protection or disease susceptibility in periodontitis have not been described. Methods Subjects (n = 278) were classified as healthy, gingivitis, or periodontitis and categorized as mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…It is well known that the carrier rate of Aa is high in young individuals and decreases with age and that of Pg changes conversely 45 . A previous study reported that in the older group of individuals, antibody titer against Pg was elevated, while that against Aa was unchanged 46 . Our study found no correlation between age and antibody titers against Aa and Pg (Supplemental Table S1 ).…”
Section: Discussionmentioning
confidence: 89%
“…It is well known that the carrier rate of Aa is high in young individuals and decreases with age and that of Pg changes conversely 45 . A previous study reported that in the older group of individuals, antibody titer against Pg was elevated, while that against Aa was unchanged 46 . Our study found no correlation between age and antibody titers against Aa and Pg (Supplemental Table S1 ).…”
Section: Discussionmentioning
confidence: 89%
“…Additionally, Gunsolley et al 87 reported that IgG2 was a dominate antibody response to Aggregatibacter actinomycetemcomitans with genetic effects in juvenile periodontitis. Thus, we can also associate the Ig gene changes in the nonhuman primates with antibody data from human periodontitis and aging 88 . These findings showed the most frequent antibody response changes to oral bacteria in disease were in the IgG2 and IgG4 subclasses, while age effects were seen in IgG1, IgG2, and IgG4 antibody levels.…”
Section: Discussionmentioning
confidence: 92%
“…13,[25][26][27][28] The population differences in disease also show enhanced disease with aging, in males, and within minority populations. [29][30][31] We have recently shown significant differences in antibody diversity 19 and IgG subclass distribution response 32 that parallel this enhanced disease expression. However, how these antibody molecules may reflect and affect disease prevention and/or resolution remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…initially, no direct connection to osteolysis, the major concern in periodontitis, was described ( 106 ). More recently, anti-carbamylated LL37 autoantibodies have been linked to an increase in bone resorption in RA ( 107 ). Auto-immunity and periodontitis are connected in many ways.…”
Section: Can Antimicrobial Peptides Affect the Function Of B-cells In...mentioning
confidence: 99%
“…In addition, AMPs’ participation in autoimmunity has been investigated in the past few years. High concentrations of AMPs have been found in sera of Lupus patients or the joints of RA patients ( 107 , 111 , 112 ). For now, AMPs’ immunomodulatory role in autoimmunity is not fully understood, probably due to the difficulty in overcoming AMPs/cytokines/chemokines’ roles redundancy combined with dual detrimental and protective effects ( 113 , 114 ).…”
Section: Can Antimicrobial Peptides Affect the Function Of B-cells In...mentioning
confidence: 99%